The relationships between external and internal training loads in mixed martial arts - Kirk, C.; Langan-Evans, C.; Clark, D. R.; Morton, J. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose As a multidisciplined combat sport, relationships between external and internal training loads and intensities of mixed martial arts (MMA) have not been described. The aim of this study was to determine the external loads and intensities of MMA training categories and their relationship to internal loads and intensities.